Glass matrix composites for transparent security measures - Boccaccini, Aldo R.; McPhail, David; Pang, Bo (Materials World, 2011)
The work at Imperial College London is processing and characterizing a range of opto-mechanical composites with a focus on alumina fiber-reinforced borosilicate glass matrix composites. In a typical experiment, oxalic acid solution is slowly poured into zirconyl chloride octahydrate solution and mixed under constant stirring. The air inside the fiber bundle can be evacuated using a vacuum pump. As the air is extracted, the sol is seen to bubble. Coated fibers are heat treated at 500°C for three hours at a slow heating rate of one degree per minute to diminish surface cracking. Sintering occurs at 1300°C after this calcination step. A hybrid sol-gel coating method has been developed to improve the coated surface's quality. After surface treatment, the composite exhibits qualitatively good transparency. The average strength of the composites is found to be in the range 30-4OMPa, with decreased spacing and increased fiber content resulting in a slightly higher average flexural strength.
UnivIS-Import:2015-03-09:Pub.2011.tech.IW.LM.glassm